2015
DOI: 10.4081/rr.2015.5854
|View full text |Cite
|
Sign up to set email alerts
|

A case of Henoch-Schönlein purpura with cardiopulmonary involvement

Abstract: Henoch-Shönlein purpura (HSP) commonly affects the kidney, causing hematuria and Immunoglobulin A type nephropathy. Extrarenal involvements are rare but can be life threatening if missed. Cardiac involvement has been described only in a handful of case reports. Although HSP is predominantly a pediatric disease, it should not be overlooked in older patients presenting with typical triad of symptoms. We report a rare case of HSP with both cardiac of pulmonary systems involvement and his clinical progress

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Extra renal involvement is rare but can be life threatening if diagnosis is missed. Direct evidence of HSP related CM are lacking but case reports of cardiopulmonary involvement [109][110][111][112] and cardiac involvement [113,114] suggest CM of an ischaemic origin in HSP patients. Lecutier [113] described a case report of an 11-year old boy who died one month after the onset of HSP.…”
Section: Pathophysiologymentioning
confidence: 99%
See 3 more Smart Citations
“…Extra renal involvement is rare but can be life threatening if diagnosis is missed. Direct evidence of HSP related CM are lacking but case reports of cardiopulmonary involvement [109][110][111][112] and cardiac involvement [113,114] suggest CM of an ischaemic origin in HSP patients. Lecutier [113] described a case report of an 11-year old boy who died one month after the onset of HSP.…”
Section: Pathophysiologymentioning
confidence: 99%
“…The study concluded that coronary spasm was the likely cause of transient myocardial ischaemia in the two patients [111]. Tan [109] reports a case of adult onset of HSP in a 60-year old woman who developed ST elevation myocardial infarction (STEMI) and pulmonary haemorrhage in the course of the disease. Prompt normalization of ST segment change suggested transient ischemic of the myocardium possible due to coronary artery spasm precipitated by vasculitis process, which causes injury to coronary vessels endothelium and releases vasoconstrictive substances from those cells (endothelin-1) that is known to possess potent vasoconstrictive actions [115].…”
Section: Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations